POTENSI PENGEMBANGAN ENERGI BARU DAN ENERGI TERBARUKAN DI KOTA SEMARANG - Jawoto Sih Setyono; Fadjar Hari Mardiansjah; Mega Febrina Kusumo Astuti (Jurnal Riptek, 2019)
Semarang is the largest metropolitan city in Central Java, Indonesia with a high electricity consumption to support community activities, Main electricity of Semarang City is supplied by the State Electricity Company (PLN), and sourced from fossil fuels which are in fact unsustainable and high risk of environmental damage. The national government attempt to reduce dependence on fossil fuels by establishing a National Energy Policy (KEN) to increase the utilization of renewable energy (EBT) by around 23% in 2025 and 31% in 2050. To support this target, local governments need play a role to realize the utilization of EBT in their respective regions. The purpose of this study is to identify the source of EBT in Semarang which has the greatest potential to be developed as an energy substitute for electricity supply. This study uses quantitative descriptive methods and Geographic Information Systems (GIS) analysis to identify the potential of EBT in each region. The results of this study indicate that solar panels are the largest potential source of EBT with an estimated substitution in 2025 is about 19% of the total electricity demand in Semarang and 12% in 2050.